Environmental Governance in Latin America:Towards an Integrative Research Agenda - Hogenboom, Bárbara (2012)
Latin America plays an important international role with regard to environmental governance. Knowledge generated by empirical and theoretical studies on environmental challenges can support the renewed efforts in the region to achieve equitable and sustainable natural resource use. Although linkages be-tween social and environmental dimensions have been academically explored since the 1990s new trends in environmental governance in Latin America deserve a comprehensive analytical approach. The authors argue that in or-der to enhance “Latin American perspectives” to solving socio-environmental dilemmas, several research streams need to be brought together in integrative frameworks  that  can  address  complex  questions  related  to  interactions  between state, civil society and market actors on multiple scales.